Longitudinal study of caries progression in 2‐ and 3‐year‐old German children. Issue 4 (19th February 2016) - Pitchika, Vinay; Kokel, Claudia; Andreeva, Jana; Crispin, Alexander; Hickel, Reinhard; Garcia‐Godoy, Franklin; Kühnisch, Jan; Heinrich‐Weltzien, Roswitha
Abstract: Objective: This 2‐year longitudinal study in 2‐ and 3‐year‐old kindergarten children investigated lesion progression on different surfaces of primary teeth. Methods: The study was conducted between September 2008 and September 2010 on a sample of 400 children from the Kyffhäuser district (Thuringia, Germany). A calibrated investigator recorded (non)cavitated caries lesions according to World Health Organization (WHO), International Caries Detection and Assessment System (ICDAS) and Universal Visual Scoring System (UniViSS) criteria. Nonparametric methods and linear regression using a mixed‐effects model with an unbalanced design were used for data analysis. Results: There was a significant increase in the prevalence of noncavitated caries lesions during the 2‐year period, with the highest chance for change on all surfaces compared to cavitated lesions. First visible sign lesions on occlusal surfaces had the highest chance for change (estimate 0.38), whereas established lesions revealed the highest chance for change on proximal (estimate 1.05) and smooth surfaces (estimate 0.62). Proximal lesions exhibited the greatest chance for change irrespective of severity level. Conclusion: Our study demonstrated that each type of carious lesion had different changing rates. Greater lesion severity correlated with greater chances to change and receive treatment. This information is crucial for dental practitioners in decision‐making processes.